Gender-specific association of NFKBIA promoter polymorphisms with the risk of sporadic colorectal cancer - Tan, Shing Cheng; Mohd Shafi’i, Mohd Suzairi; Abdul Aziz, Ahmad Aizat; Mustapha, Mohd Aminudin; Siti Nurfatimah, Mohd Shahpudin; Venkata Murali, Krishna Bhavaraju; Biswal, Biswal Mohan; Ravindran, Ankathil (Springer US, 2013)
The inhibitory protein IκBα, encoded by the NFKBIA gene, plays an important role in regulating the activity of nuclear factor-kappa B, a transcription factor which has been implicated in the initiation and progression of cancers. This study aimed to evaluate the association of NFKBIA −826C>T (rs2233406) and −881A>G (rs3138053) polymorphisms with the risk of sporadic colorectal cancer (CRC) in Malaysian population. A case–control study comprising 474 subjects (237 CRC patients and 237 cancer-free controls) was carried out. The polymorphisms were genotyped from the genomic DNA of the study subjects employing PCR–RFLP, followed by DNA sequencing. The association between the polymorphic genotypes and CRC risk was evaluated by deriving odds ratios (ORs) and 95 % confidence intervals (CIs) using unconditional logistic regression analysis. The two polymorphisms were in complete and perfect linkage disequilibrium (D′ = 1.0, r 2 = 1.0). Overall, no statistically significant CRC risk association was found for the polymorphisms (P > 0.05). A similar lack of association was observed when the data were stratified according to ethnicity (P > 0.05). However, stratification by gender revealed a significant inverse association between the heterozygous genotype of the polymorphisms and the risk of CRC among females (OR 0.53, 95 % CI 0.29–0.97, P = 0.04), but not among males (P > 0.05). In conclusion, the heterozygous genotype of the polymorphisms could contribute to a significantly decreased CRC risk among females, but not males, in the Malaysian population.